Prevalencia de uso de cannabis: perfil familiar y social de una muestra adolescente (2016)
This study described and established differences in the structural/dynamic family and social profile of adolescents according to the lifetime prevalence of cannabis. Quantitative, descriptive and cross-sectional study. Non-random sample of 156 adolescents included in secondary education. Low family support, less confidence and consumption of illegal substances characterized the dynamics of families of who have tried cannabis at least once in life. A greater number of friends of who have ever used cannabis use more cannabis, alcohol, tobacco and other substances. Couples of who have used cannabis not function as a protective factor as they consume more substances that couples who have never tried cannabis. Cannabis prevention programs have to do a greater emphasis on the work of the dynamic aspects of families and relationships of adolescents with their peers including their partners.